A 3D, map based approach to reconstruct and calibrate palaeo-bathymetries – Testing the Cretaceous water depth of the Hammerfest Basin, southwestern Barents Sea. (1st April 2015) - Emmel, B.; de Jager, G.; Zieba, K.; Kurtev, K.; Grøver, A.; Lothe, A.; Lippard, S.J.; Roli, O.A.
Abstract: A new 3D approach to quantify and calibrate palaeo-water depth (PWD) has been applied to evaluate the Aptian to Maastrichtian/Danian (Cretaceous) bathymetric development in a sub-basin scale within the Hammerfest Basin, southwestern Barents Sea. The results indicate PWD's varying between ca. 200 m and 95 m, recording a local sea-level decrease of ca. 105 m. A calibration against shale volume based on gamma-ray logs from four exploration wells indicates a model sensitivity of ca. +50 m and −150 m. These results are in agreement with empirical PWD estimates obtained from sedimentological and micropalaeontological observations. A comparison with the global eustatic sea level curve indicates that the PWD decrease in the Hammerfest Basin contradicts the general, global trend indicating a primary control by local tectonics such as differential subsidence and uplift along the evolving continental margin offshore north-west Norway. Highlights: A new approach to reconstruct and calibrate palaeo-bathymetries was tested in the Barents Sea. Modeled Cretaceous bathymetry of the Hammerfest Basin is in agreement with estimates based on sedimentology and micropalaeontology. Late Cretaceous bathymetric modification as a response to uplift in the Hammerfest Basin.